Wideband tunable mid-infrared cross-polarisation converter using monolayered graphene-based metasurface over a wide angle of incidence - Yadav V.S.; Ghosh S.K.; Das S.; Bhattacharyya S. (My University, 2025)
In this study, the authors have designed and proposed a monolayer graphene-based metasurface, performing as a broadband polarisation converter over a wide angle of incidence. The unit cell of the metasurface consists of split ring generated over a perforated single layer of graphene grown over metal-backed silicon dioxide. The structure converts incident linearly polarised wave into its cross-polarised component over a wide bandwidth with peak polarisation conversion exhibits value to unity. The plane of polarisation of the incident electromagnetic wave is rotated orthogonally on reflection from the proposed metasurface over full width at half maxima bandwidth around 72.83% compared with centre frequency of 2.16 THz, which can be maintained up to 40° incident angles under both transverse electric and transverse magnetic polarisations. The proposed structure is as thin as -λ/7.3 with respect to lowermost frequency and the period of the structure is about λ/10.7. The frequency band of polarisation conversion can be tuned by altering chemical doping as well as the electrostatic grating of the graphene sheet. The structure can find applications toward sensing, spectroscopy etc. © The Institution of Engineering and Technology.